Preference of methadone maintenance patients for the integrative and decentralized service delivery models in Vietnam - Nguyen, Hoang Long (BioMed Central, 2016)
Background:Integrating and decentralizing services are essential to increase the accessibility and provide comprehensive care for methadone patients. Moreover, they assure the sustainability of a HIV/AIDS prevention program by reducing the implementation cost. This study aimed to measure the preference of patients enrolling in a MMT program for integrated and decentralized MMT clinics and then further examine related factors. Methods:A cross-sectional study was conducted among 510 patients receiving methadone at 3 clinics in Hanoi. Structured questionnaires were used to collect data about the preference for integrated and decentralized MMT services. Covariates including socio-economic status; health-related quality of life (using EQ-5D-5 L instrument) and HIV status; history of drug use along with MMT treatment; and exposure to the discrimination within family and community were also investigated. Multivariate logistic regression with polynomial fractions was used to identify the determinants of preference for integrative and decentralized models. Results:Of 510 patients enrolled, 66.7 and 60.8 % preferred integrated and decentralized models, respectively. The main reason for preferring the integrative model was the convenience of use of various services (53.2 %), while more privacy (43.5 %) was the primary reason to select stand-alone model. People preferred the decentralized model primarily because of travel cost reduction (95.0 %), while the main reason for not selecting the model was increased privacy (7.7 %). After adjusting for covariates, factors influencing the preference for integrative model were poor socioeconomic status, anxiety/depression, history of drug rehabilitation, and ever disclosed health status; while exposure to community discrimination inversely associated with this preference. In addition, people who were self-employed, had a longer duration of MMT, and use current MMT with comprehensive HIV services were less likely to select decentralized model. Conclusion:In conclusion, the study confirmed the high preference of MMT patients for the integrative and decentralized MMT service delivery models. The convenience of healthcare services utilization and reduction of geographical barriers were the main reasons to use those models within drug use populations in Vietnam. Countering community stigma and encouraging communication between patients and their societies needed to be considered when implementing those models.